2017
DOI: 10.5740/jaoacint.16-0330
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric Methods for Simultaneous Determination of Sofosbuvir and Ledipasvir (HARVONI Tablet): Comparative Study with Two Generic Products

Abstract: Sofosbuvir and ledipasvir are the first drugs in a combination pill to treat chronic hepatitis C virus. Simple, sensitive, and rapid spectrophotometric methods are presented for the determination of sofosbuvir and ledipasvir in their combined dosage form. These methods were based on direct measurement of ledipasvir at 333 nm (due to the lack of interference of sofosbuvir) over a concentration range of 4.0-14.0 µg/mL, with a mean recovery of 100.78 ± 0.64%. Sofosbuvir was determined, without prior separation, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Statistical comparisons between the results of the proposed method on pharmaceutical dosage forms and those of reported methods [ 27 , 31 , 38 ] were carried out using Student’s t -test for accuracy and F -test for precision. As shown in Table 6 , the calculated t -test and F -values did not exceed the tabulated one at the 95% confidence level, revealing that there was no significant difference between the proposed and reported methods with respect to accuracy and precision.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical comparisons between the results of the proposed method on pharmaceutical dosage forms and those of reported methods [ 27 , 31 , 38 ] were carried out using Student’s t -test for accuracy and F -test for precision. As shown in Table 6 , the calculated t -test and F -values did not exceed the tabulated one at the 95% confidence level, revealing that there was no significant difference between the proposed and reported methods with respect to accuracy and precision.…”
Section: Resultsmentioning
confidence: 99%
“…Several methods for the simultaneous determination of SF either with LD [ 19 , 33 , 34 , 35 , 36 , 37 , 38 ] or with SM have been published [ 13 ]. A single method has been published for the simultaneous determination of SF, LD, DC, and SM in plasma [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The adopted methods were also validated as per ICH guidelines and statistically compared to an inhouse HPLC method. 25 Abo T et al 26 has developed spectrophotometric methods for simultaneous determination of Sofosbuvir and Ledipasvir . These methods were based on direct measurement of ledipasvir at 333nm.…”
Section: Tablementioning
confidence: 99%
“…The analytical method was validated for various parameters as per ICH guidelines. 26 Chromatographic methods: The high performance liquid chromatography (HPLC) method has been reported for the analysis of Sofosbuvir in pharmaceutical formulation, bulk as well as in biological fluids.…”
Section: Tablementioning
confidence: 99%
“…A literature review revealed a few methods have been reported for the quantitative determination of DAC and LED alone or in combination with other drugs. These include spectrophotometric, spectrofluorimetric, HPLC,, LC–MS/MS and electrochemical methods . The extensive use of the newly discovered antiviral drugs for the treatment of HCV necessitates the need to develop a cheap, rapid bio‐analytical method for their routine measurement in biological samples.…”
Section: Introductionmentioning
confidence: 99%